Monkeypox- need for Vigilant Health system and Regulations towards a Global Health Threat - Jain, Seema (Indian Journal of Community Health, 2024)
A viral illness caused by the monkey pox virus, monkeypox is now known as Mpox. It is a zoonotic infectious disease causing painful rash, enlarged lymph nodes, fever, headache, muscle ache, backpain and low energy. According to WHO, most cases in 2022 were in Africa but later m-pox was reported from USA, Europe Australia & Canada. Mpox continues to be a threat today, with upsurge of cases in Democratic Republic of Congo and other countries in Africa. Since 2022, there has also been an upsurge in mpox cases and deaths in the Democratic Republic of the Congo. Over 120 countries have reported mpox between Jan 2022-Aug 2024, with over 1,00,000 laboratory-confirmed cases reported and over 220 deaths among confirmed cases. In India, MoHFW reported 30 cases in the last 2022 outbreak, with last case occurring in March 2024. The monkeypox virus was discovered in Denmark (1958) in monkeys kept for research. The first reported human case of mpox was a nine-month-old boy in the Democratic Republic of the Congo (1970). Mpox steadily emerged in central, east and west Africa following the eradication of smallpox in 1980 and the end of smallpox vaccination worldwide. In 2003, there was an outbreak in the United States of America, linked to imported wild animals. Since 2005, thousands of cases are reported in the Democratic Republic of the Congo every year. In May 2022, an outbreak of mpox appeared suddenly and rapidly spread across Europe, the Americas and then all six WHO regions including refugee camps in the Republic of the Sudan.